Effects of APOC3 Heterozygous Deficiency on Plasma Lipid and Lipoprotein Metabolism. Issue 1 (January 2019) - Reyes-Soffer, Gissette; Sztalryd, Carol; Horenstein, Richard B.; Holleran, Stephen; Matveyenko, Anastasiya; Thomas, Tiffany; Nandakumar, Renu; Ngai, Colleen; Karmally, Wahida; Ginsberg, Henry N.; Ramakrishnan, Rajasekhar; Pollin, Toni I.
Abstract : Objective—: Apo (apolipoprotein) CIII inhibits lipoprotein lipase (LpL)-mediated lipolysis of VLDL (very-low-density lipoprotein) triglyceride (TG) and decreases hepatic uptake of VLDL remnants. The discovery that 5% of Lancaster Old Order Amish are heterozygous for the APOC3 R19X null mutation provided the opportunity to determine the effects of a naturally occurring reduction in apo CIII levels on the metabolism of atherogenic containing lipoproteins. Approach and Results—: We conducted stable isotope studies of VLDL-TG and apoB100 in 5 individuals heterozygous for the null mutation APOC3 R19X (CT) and their unaffected (CC) siblings. Fractional clearance rates and production rates of VLDL-TG and apoB100 in VLDL, IDL (intermediate-density lipoprotein), LDL, apo CIII, and apo CII were determined. Affected (CT) individuals had 49% reduction in plasma apo CIII levels compared with CCs ( P <0.01) and reduced plasma levels of TG (35%, P <0.02), VLDL-TG (45%, P <0.02), and VLDL-apoB100 (36%, P <0.05). These changes were because of higher fractional clearance rates of VLDL-TG and VLDL-apoB100 with no differences in production rates. CTs had higher rates of the conversion of VLDL remnants to LDL compared with CCs. In contrast, rates of direct removal of VLDL remnants did not differ between the groups. As a result, the flux of apoB100 from VLDL to LDL was not reduced, and the plasma levels of LDL-cholesterol and LDL-apoB100 were not lower in the CT group. Apo CIII production rate was lower in CTs compared with CCs, whereas apo CII production rate was not different between the 2 groups. The fractional clearance rates of both apo CIII and apo CII were higher in CTs than CCs. Conclusions—: These studies demonstrate that 50% reductions in plasma apo CIII, in otherwise healthy subjects, results in a significantly higher rate of conversion of VLDL to LDL, with little effect on direct hepatic uptake of VLDL. When put in the context of studies demonstrating significant protection from cardiovascular events in individuals with loss of function variants in the APOC3 gene, our results provide strong evidence that therapies which increase the efficiency of conversion of VLDL to LDL, thereby reducing remnant concentrations, should reduce the risk of cardiovascular disease. Abstract : Supplemental Digital Content is available in the text.